Creating work motivation for Sales staffs at Truong Hai Automobile Joint stock company = Tạo động lực làm việc cho nhân viên kinh doanh tại công ty cổ phần ô tô Trường Hải - Ngô, Thị Hiền (2020)
Research objectives: Systematize the basic issues of motivation and motivation creation for employees. Study the factors influencing the work motivation creation for employees. Analyze and assesse the current status of creating work motivation for sales staffs at Truong Hai Automobile Joint Stock Company-Identify the factors that affect the work motivation of sales staff at Truong Hai Automobile Joint Stock Company-Propose solutions and recommendations to increase work motivation for staffs and bring efficiency to the Company in the next time